The evaluation of effect of non-operative methods for stress urinary incontinence treatment in women with use of different diagnostic methods - Wlaźlak, Edyta; Surkont, Grzegorz; Stetkiewicz, Tomasz; Wrońska, Barbara; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2004)
Nowadays in urogynecology there are many diagnostic methods. Till now their full clinical significance is yet to be established. Because we do not have ideal diagnostic and operative methods for stress urinary incontinence treatment, most of the women should be at first treated with non-operative methods. Aim of the study was to evaluate effects of non-operative methods of stress urinary incontinence treatment with use of different diagnostic methods. Fifty patients with symptoms of stress urinary incontinence I, II and III degree were evaluated in this study. On second visit after 6 months 46 patients were diagnosed. As treatment tool there were used Kegel excercises. In postmenopausal women with pH>5 there was also estrogen intravaginal treatment established. To evaluate effects of therapy we used different urogynecology methods. With use of different methods we found that 6.5% to 58.6% patients were successfully treated.